Helically and Linearly Fused Rylenediimide-Hexabenzocoronenes - Dusold, Carolin; Haines, Philipp; Platzer, Benedikt; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2021)
Perylene- as well as naphthalenediimides were fused to hexabenzocoronenes (HBCs) at their imide position to realize highly π-extended donor–acceptor (D–A)-hybrids. Successful isomer separation in the first step was decisive to guarantee a straightforward synthetic sequence. Hexaphenylbenzenes as precursors were accessed via Diels–Alder reactions and reacted in a Scholl oxidation to yield the respective HBC derivatives. The fully conjugated benzimidazole linker, which separates the electron donating HBC from the electron accepting rylenediimide, enabled the formation of either a linear or a helical configuration. Largely different chemical, physical, and optoelectrical characteristics were noted for the two configurations. What stood out was their aggregation and their excited state deactivation depending on the solvent polarity. Results from global analysis of the femtosecond transient absorption data corroborated the formation of a charge-transfer (CT) state that is stabilized in the helically fused configuration relative to the linear analogue. However, a comparison with spectroelectrochemical experiments failed to disclose evidence for a charge-separated (CS) state.
CRIS-Team Scopus Importer:2021-03-19
Keywords: charge transfer; helicene; hexabenzocoronene HBC; rylenediimide; transient absorption